CREATING HEALTH MEDIA BASED ON SOCIAL MEDIA IN COLLABORATION WITH PUBLIC CENTRE IN MALANG - Rakhmani, Alidha Nur; Rahayu, Indriati Dwi; Setijowati, Nanik; Rusnianah, Farida (Caring: Jurnal Pengabdian Masyarakat, 2024)
Ease of access to health information services that are in accordance with community needs can increase awareness of the importance of health so that healthy habits and lifestyles are formed. However, obstacles can arise in obtaining the right information due to ignorance or lack of understanding of health information. One effort to minimize this is to provide health information to the public through social media, especially podcasts. Primary health care (Puskesmas) as health service providers have work areas and programs in the community, one of which is health promotion efforts. This program can be used to support health programs. The use of social media is considered important, because health topics are quite popular among netizens who use social media. This community service is in collaboration with 6 Puskesmas in Malang City. This activity has succeeded in creating three health podcast video contents together with Puskesmas.